Redes de apoyo social para la permanencia de los estudiantes del 5to ciclo de las carreras de la Universidad Politécnica Salesiana, sede Cuenca, 2019-2020 - Pauta Sigsig, Carmen Dolores (2020)
Social support networks are a necessary tool for the development of people, they are a fundamental part of the well-being and satisfaction of needs of university level students. The objective of this article is to identify the social support networks that allow the permanence of 5th cycle students.